Treading Angels: Edinburgh and its Festivals. Issue 3 (August 2019) - McCrone, David
Abstract : How did Edinburgh become 'festival city'? Despite appearances, it was not always so, and it acquired the accolade by happenstance; in the view of one observer, a 'strange amalgam of cultural banditry, civic enterprise and idealism'. The official Festival's survival was down to the City Council, and it was funded almost entirely by public bodies. This was the central structure around which The Fringe developed, and The Traverse prospered, along with smaller festivals and events to become Festival City. The story sheds considerable light on how Edinburgh 'works', its strengths and weaknesses combined.